2016
DOI: 10.1186/s12978-016-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Fertility awareness and attitudes towards parenthood among Danish university college students

Abstract: BackgroundPostponing parenthood has steadily increased during the past decades in Western countries. This trend has affected the size of families in the direction of fewer children born per couple. In addition, higher maternal age is associated with an increased risk of pregnancy-related complications such as prematurity and foetal death, while higher paternal age increases the risk of miscarriage and affects time-to-pregnancy. Hence, understanding the circumstances and reflections that influence the decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 27 publications
6
75
1
2
Order By: Relevance
“…This finding of this investigation differs from that of previous studies performed with university students. In many studies knowledge levels of female students were reportedly higher [13,15,19] , however Sørensen et al [20] reported lack of any difference in knowledge levels between male, and female students. The difference favouring male students, was thought to be related to increased sexual experience, and higher frequency of sexual intercourse among male students.…”
Section: Discussionmentioning
confidence: 99%
“…This finding of this investigation differs from that of previous studies performed with university students. In many studies knowledge levels of female students were reportedly higher [13,15,19] , however Sørensen et al [20] reported lack of any difference in knowledge levels between male, and female students. The difference favouring male students, was thought to be related to increased sexual experience, and higher frequency of sexual intercourse among male students.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of these factors, research suggests that men and women may also delay parenthood based on a lack of accurate information about the reproductive life span and the consequences of delaying parenthood . Recognizing men's role in decision‐making about timing of parenthood, several studies have examined men's fertility knowledge . These studies have shown that men have critical gaps in their knowledge on fertility issues and assisted reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that men have critical gaps in their knowledge on fertility issues and assisted reproduction. For example, men underestimate the impact of the age‐related decline in fertility in women and overestimate the success rates of fertility treatment . Men also lack knowledge about risks to fertility, the impact of age on male fertility, and the incidence of infertility …”
Section: Introductionmentioning
confidence: 99%
“…Among suggested reasons for postponing parenthood are the ability to prevent and plan pregnancy with simple and effective contraceptive methods, problems by finding a suitable partner, women pursuing education and career before parenthood, and increased prosperity [2]. …”
Section: Introductionmentioning
confidence: 99%